Pengaruh Media Wordwall Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SDN Gugus X Kota Bengkulu - Anita, Teri; Yuliantini, Nani; Susanti, Atika (JURIDIKDAS, 2025)
This study aims to determine the effect of using Wordwall media on reading comprehension skills of fifth grade students in cluster ten Bengkulu City. This type of research is quantitative research and the method used is quasy experimental method with The Matching Only Pretest-Posttest Group Design research design. The population in this study was public elementary school in cluster ten of Bengkulu City. The samples in this study were fifth grade students of public elementary school 58 of Bengkulu City as the experimental group using Wordwall media and fifth grade students of public elementary school 15 Bengkulu City as the control group using media in the form of powerpoint. The research instrument used a test in the form of multiple choice questions. The data analysis used was descriptive analysis, prerequisite test, and inferential analysis, namely t-test. These results are evidenced by the value of tcount = 7.255 and the value of Sig. (2-tailed) value is 0.000 and the ttable distribution value is 2.015. So that the value of tcount> ttable (7.255> 2.015) and Sig. (2-tailed) of 0.000 <0.05. then H0 is rejected and Ha is accepted. This is based on the difference in treatment between the experimental group and the control group. Thus, from the results of this study it can be concluded that there is an effect of using Wordwall media on the reading comprehension ability of fifth grade students in cluster ten of Bengkulu City.